Διερεύνηση των γνώσεων και των στάσεων των μαιών και νοσηλευτών/τριών για το θηλασμό και των απόψεων τους για την εφαρμογή των «δέκα βημάτων» για εγκαθίδρυση και επιτυχή θηλασμό στα μαιευτήρια της Λευκωσίας - Τρύφωνος, Φροσούλα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction: The 'Ten Steps' is a reliable method for successful launch, continuation and support of breastfeeding. Worldwide research data highlight the importance of the contribution of midwives/nurses to support the mother-infant relationship in the initiation, duration and support the establishment of exclusive breastfeeding. They also reveal deficiency or gaps in breastfeeding knowledge, as well as the misinformation and misguidance the mothers receive from the health professionals. In Cyprus, the breastfeeding rates are low, however, there is lack of research data. Aim: To investigate, present and describe the current situation regarding practices in the maternity units in Nicosia regarding the protection, promotion and support of breastfeeding by exploring the views of staff to implement the "Ten Steps". To explore their knowledge and attitudes about breastfeeding and the correlation with demographic factors Material and Method: A descriptive study was used to collect data for comparison (between Public and private sector) and correlation (knowledge and attitudes) using anonymous self-administered questionnaire. The survey was conducted in all maternity units in Nicosia. The sample was all the midwives and nurses working in the units. The breastfeeding questionnaire (Ingram, 2006) and the Self-Appraisal of compliance of obstetric units practices in the implementation of the "Ten Steps» - WHO/UNICEF were used. Data collection was performed during January-March 2014. Results: Sample number was 93 nurses/midwives providing a response rate of 77.9% in public sector and 46.8% in private sector (total response rate 62%). High implementation was found in Steps 5 (0.840.20), 8 (0.860.27) and 3 (0.660.26) (teaching, encouragement of breastfeeding, inform pregnant women about benefits and management of breastfeeding). Low adherence in Steps 1 (0.430.28), 2 (0.530.28) and 7 (0.510.43) (written breastfeeding policy, education of health professionals and rooming in). Regarding the Compliance with the International Code of Marketing of Breast-milk Substitutes, code 7 had the higher percentage with 69.9% and code 1 had the lower with 24.7%. Factor analysis performed for Breastfeeding Questionnaire resulting into three factors with Cronbach’s alpha rating from 0,58 to 0,83. Health professionals in public sector have higher scores in knowledge and attitudes regarding breastfeeding. The “knowledge” factor observed to have the highest difference (public:23.00 3.57, private:20.793.45, p-value=0.005). Health professionals with master’s or doctoral’s degree have higher scores (factor 1: p-value=0.008, Factor 2: p-value0.001, Factor 1 «knowledge»: p-value=0.004). Midwives have higher level of knowledge and more positive attitudes’ scores concerning breastfeeding in comparison with the other health professionals. Conclusions: No fully compliance observed and the overall implementation was rated as “moderate to low.” Step 3 is most implemented in public sector whether Step 4 is most implemented in private sector. Low implementation rates in the Compliance with the International Code of Marketing of Breast-milk Substitutes as well as low level of knowledge and poor attitude towards breastfeeding practices in both public and private sector observed. In private sector the level of knowledge was lower. Midwives have higher level of knowledge and more positive attitude regarding breastfeeding practices in comparison with the other health care professionals. Overall there was a positive statistical correlation of knowledge and attitudes with the level of education. A validated tool for the exploration of knowledge and attitudes about breastfeeding was emerged, which may trigger additional researches and add useful findings to the knowledge field. There is a need of a written policy regarding breastfeeding practices that is that is routinely communicated to all health care staff (Step 1).
Keywords: Ten Steps; Breastfeeding; Establishment; Midwives; Maternity Units; Δέκα βήματα; Μητρικός Θηλασμός; Εγκαθίδρυση; Μαίες; Μαιευτικές Μονάδες